Livestock development policies in the humid and sub-humid zones of Sub-Saharan Africa: proceedings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Factors involved in formulating livestock development policies, identifying information gaps in policy formulation, and promoting national and international consensus on resources utilisation, socio-economic policies and the institutional environment need